A New Topology of Parallel Current Source Applied for Li-Ion Battery Charger - Nguyen-Van, Hao; Nguyen, Minh; Pham-Nguyen, Loan (Old Journal, 2017)
In this paper, a design approach of long-life Li-lon battery charger is presented. To produce charging current according to the Li-lon battery charging process, a new topology of parallel current source is proposed. This topology allows to attain low trickle current in the pre-charge state while the large current state can be guaranteed at high level and that results in a significant reduction of damage to Li-Ion battery. Moreover, the charging mode control signals are more stable by introducing a hysteresis comparator into the charging mode controller. This Li-Ion battery charger is designed based on 0.13 um CMOS technology and simulated by Cadence. The post-layout simulation results shown a good performance in which the charging process is terminated at a battery voltage of 4.2 V and a charging current of 43 mA. The simulated trickle current is approximately 203 mA and the maximum charging current reaches 975 mA. The designs offer an average power efficiency of 92.2% is obtained with battery voltage varying from 2.9 V to 4.2 V.